PENERAPAN RELIABILITY CENTERED MAINTENANCE PADA PERALATAN SHIP UNLOADER PLTU TENAYAN 2 X 110 MW - Yudha Prasetyo; Japri Lukman (Research Center University of Pahlawan Tuanku Tambusai, 2020)
Abstract The Tenayan Steam Power Plant (PLTU) is a fossil fuel power plant that is coal with a low rank coal type. To be able to meet the needs of electricity on the island of Sumatra, especially the Riau and Riau Islands, the Tenayan power plant must maintain coal needs within a safe range of 15-25 days of operation. Coal needs may not experience a decrease in productivity due to equipment damage. The obstacle that arises is the frequent occurrence of unexpected downtime which results in disrupted coal production so that the supply of coal is insufficient for the unit to operate so that the unit must be derating. This is caused by damage to one of the coal dismantling equipment, the ship unloader. This study aims to provide equipment maintenance and optimal inspection time intervals on ship unloader equipment. The research method used is Reliability Centered Maintenance (RCM) with quantitative analysis. After analysis, it was found that the critical component of the Tenayan PLTU ship unloader was the chain bucket. This is obtained based on the component with the most damage frequency, which is 16 damage over a 3-year period. From the results of data processing, the MTTR value is 62.72 hours and MTTF is 211.02 hours, while the optimal inspection time interval is 6 days, so it is recommended to do reactive, inspection, and preventive maintenance activities on the chain bucket periodically every 6 days in order to increase the reliability of the chain bucket.